Spontaneous Osteogenic Differentiation of Human Mesenchymal Stem Cells by Tuna-Bone-Derived Hydroxyapatite Composites with Green Tea Polyphenol-Reduced Graphene Oxide - Moon Sung Kang; Rowoon Park; Hyo Jung Jo; Yong Cheol Shin; Chang-Seok Kim; Suong-Hyu Hyon; Suck Won Hong; Junghwan Oh; Dong-Wook Han (Cells, 2023)
In recent years, bone tissue engineering (BTE) has made significant progress in promoting the direct and functional connection between bone and graft, including osseointegration and osteoconduction, to facilitate the healing of damaged bone tissues. Herein, we introduce a new, environmentally friendly, and cost-effective method for synthesizing reduced graphene oxide (rGO) and hydroxyapatite (HAp). The method uses epigallocatechin-3-O-gallate (EGCG) as a reducing agent to synthesize rGO (E-rGO), and HAp powder is obtained from Atlantic bluefin tuna (Thunnus thynnus). The physicochemical analysis indicated that the E-rGO/HAp composites had exceptional properties for use as BTE scaffolds, as well as high purity. Moreover, we discovered that E-rGO/HAp composites facilitated not only the proliferation, but also early and late osteogenic differentiation of human mesenchymal stem cells (hMSCs). Our work suggests that E-rGO/HAp composites may play a significant role in promoting the spontaneous osteogenic differentiation of hMSCs, and we envision that E-rGO/HAp composites could serve as promising candidates for BTE scaffolds, stem-cell differentiation stimulators, and implantable device components because of their biocompatible and bioactive properties. Overall, we suggest a new approach for developing cost-effective and environmentally friendly E-rGO/HAp composite materials for BTE application.